Morphological, Physiological, and Molecular Responses to Heat Stress in Brassicaceae - Iram Batool; Ahsan Ayyaz; Tongjun Qin; Xiaofen Wu; Weiqi Chen; Fakhir Hannan; Zafar Ullah Zafar; Muhammad Shahbaz Naeem; Muhammad Ahsan Farooq; Weijun Zhou (Plants)
Food security is threatened by global warming, which also affects agricultural output. Various components of cells perceive elevated temperatures. Different signaling pathways in plants distinguish between the two types of temperature increases, mild warm temperatures and extremely hot temperatures. Given the rising global temperatures, heat stress has become a major abiotic challenge, affecting the growth and development of various crops and significantly reducing productivity. Brassica napus, the second-largest source of vegetable oil worldwide, faces drastic reductions in seed yield and quality under heat stress. This review summarizes recent research on the genetic and physiological impact of heat stress in the Brassicaceae family, as well as in model plants Arabidopsis and rice. Several studies show that extreme temperature fluctuations during crucial growth stages negatively affect plants, leading to impaired growth and reduced seed production. The review discusses the mechanisms of heat stress adaptation and the key regulatory genes involved. It also explores the emerging understanding of epigenetic modifications during heat stress. While such studies are limited in B. napus, contrasting trends in gene expression have been observed across different species and cultivars, suggesting these genes play a complex role in heat stress tolerance. Key knowledge gaps are identified regarding the impact of heat stress during the growth stages of B. napus. In-depth studies of these stages are still needed. The profound understanding of heat stress response mechanisms in tissue-specific models are crucial in advancing our knowledge of thermo-tolerance regulation in B. napus and supporting future breeding efforts for heat-tolerant crops.